Spatial patterning of excitatory and inhibitory neuropil territories during spinal circuit development. Issue 7 (1st May 2017) - Yan, Qing; Zhai, Lu; Zhang, Bo; Dallman, Julia E.
Abstract: To generate rhythmic motor behaviors, both single neurons and neural circuits require a balance between excitatory inputs that trigger action potentials and inhibitory inputs that promote a stable resting potential (E/I balance). Previous studies have focused on individual neurons and have shown that, over a short spatial scale, excitatory and inhibitory (E/I) synapses tend to form structured territories with inhibitory inputs enriched on cell bodies and proximal dendrites and excitatory inputs on distal dendrites. However, systems‐level E/I patterns, at spatial scales larger than single neurons, are largely uncharted. We used immunostaining for PSD‐95 and gephyrin postsynaptic scaffolding proteins as proxies for excitatory and inhibitory synapses, respectively, to quantify the numbers and map the distributions of E/I synapses in zebrafish spinal cord at both an embryonic stage and a larval stage. At the embryonic stage, we found that PSD‐95 puncta outnumber gephyrin puncta, with the number of gephyrin puncta increasing to match that of PSD‐95 puncta at the larval stage. At both stages, PSD‐95 puncta are enriched in the most lateral neuropil corresponding to distal dendrites while gephyrin puncta are enriched on neuronal somata and in the medial neuropil. Significantly, similar to synaptic puncta, neuronal processes also exhibit medial‐lateral territories at both developmental stages with enrichment of glutamatergic (excitatory) processes laterally and glycinergic (inhibitory) processes medially. This establishment of neuropil excitatory‐inhibitory structure largely precedes dendritic arborization of primary motor neurons, suggesting that the structured neuropil could provide a framework for the development of E/I balance at the cellular level. J. Comp. Neurol. 525:1649–1667, 2017. © 2016 Wiley Periodicals, Inc.